Pancreatic Beta Cell Identity in Humans and the Role of Type 2 Diabetes - Marchetti, Piero; Bugliani, Marco; De Tata, Vincenzo; Suleiman, Mara; Marselli, Lorella (Frontiers in Cell and Developmental Biology, 2017)
Pancreatic beta cells uniquely synthetize, store and release insulin. Specific molecular, functional as well as ultrastructural traits characterize their insulin secretion properties and survival phentoype. In this review we focus on human islet/beta cells, and describe the changes that occur in type 2 diabetes and could play roles in the disease as well as represent possible targets for therapeutical interventions. These include transcription factors, molecules involved in glucose metabolism and insulin granule handling. Quantitative and qualitative insulin release patterns and their changes in type 2 diabetes are also associated with ultrastructural features involving the insulin granules, the mitochondria and the endoplasmic reticulum.